Dainik Bhaskar: The Punjab Launch - Dogra, Balram; Khara, Navjote; Verma, Rajesh (Indian Journal of Marketing, 2007)
Punjab is one market where the reach of Hindi dailies is more than that of the regional (Punjabi) newspapers. Recognizing this Dainik Bhaskar’ decided to enter the Punjab market after a successful run in Chandigarh and Haryana. Although the scope in this market is tremendous, the degree of competitiveness has changed over the last five years. Entering Punjab was a part of its overall expansion strategy and in future, the group also plans to explore the Jammu&Kashmir and Delhi markets. This case study focuses on the massive consumer hype generated by the Punjab launch of Dainik Bhaskar in October 2006 using direct marketing to establish a leadership position from day one. In the face of strong competition from well-known established newspapers in an already busy market sector, the launch of Dainik Bhaskar was not an easy task. The company did an extensive research to find out what the Hindi readers in Punjab want in a newspaper and used new and innovative marketing strategies during pre-launch and post-launch time to position the newspaper effectively in the market. The primary objective of this case is to study the different promotional activities undertaken by Dainik Bhaskar and to meet its launch objectives.